The geometrical modeling of aortic root complex - Uğurlucan, Murat; Beyaz, Metin Onur; Öztaş, Didem Melis; Öztürk, Adnan; Şahinoğlu, Kayıhan; Alpagut, Ufuk; Bozboğa, Nilgün (My University, 2019)
BACKGROUND: This study was designed to investigate the anatomical relationship of the different levels of aortic root. MATERIALS AND METHODS: The morphological features of the aortic root were examined using of 12 adult hearts from fixed male cadavers who had expired due to noncardiac causes by magnetic resonance imaging and applied mathematical analyses to the results. The measurements of the aortic root were done at four levels: at the ventriculoarterial junction (annulus), at the largest level of the Valsalva sinuses (sinus), at the level of commissures (sinotubular junction [STJ]), and at 1 cm above the STJ (aorta ascendens). We derived an equation that allows calculation of the appropriate diameter of the aortic root from four levels. Statistical analysis among the variation of the diameters at the four levels of aortic root was achieved using test one-way analysis of variance. RESULTS: The data showed a geometric pattern of the aortic root. The comparison of the values from four levels showed that the narrowest at the sinotubular junctional level and the widest at the sinus level. CONCLUSION: The analysis of our data shows that the aortic root has a consistent shape with varying size and that is a definable mathematical relationship between root diameter.
Keywords: Aortic Root; Cardiac Anatomy; Mathematical Modeling